Corticosteroid toxicity in children - Aljebab, Fahad (2017)
Corticosteroid medicines have anti-inflammatory and immunosuppressant effects. Corticosteroids are prescribed for a wide range of conditions in children. The duration of treatment ranges from a few days (short course) to long term. They are usually given orally in the different dosage form of tablets, syrup or soluble tablets. There are a wide range of adverse drug reactions (ADRs) associated with corticosteroids. This thesis initially evaluates the incidence of each individual ADR in children using systematic reviews. Prospective studies of palatability and pharmacoepidemiology using different methods are also used to evaluate aspects of using corticosteroids in children in Saudi Arabia and the UK.